Hubungan Aktivitas Fisik dengan Tekanan Darah pada Pasien Hipertensi - Ariva Firdiani; Idrawati Bahar; Yosi Suryarinilsih; Nova Yanti; Tasman Tasman (Poltekkes Kemenkes Padang, 2026)
This study shows a significant relationship between physical activity and blood pressure among hypertensive patients at Andalas Health Center, Padang City, where increased physical activity is associated with decreased systolic and diastolic blood pressure, with p-values of 0.000 and 0.001, respectively. The average physical activity of respondents was categorized as moderate (805.87 MET-minutes/week), while blood pressure was in the stage I hypertension category. The characteristics of respondents were predominantly female, with a mean age of 54.96 years; most had a family history of hypertension and experienced stress, which also influenced blood pressure conditions. These findings indicate that physical activity is an important factor in controlling hypertension. Therefore, efforts are needed to increase regular physical activity through education and health programs to prevent further complications. In conclusion, there is a significant relationship between physical activity and blood pressure in hypertensive patients, so increasing physical activity can be an effective strategy to reduce blood pressure. It is recommended that healthcare providers enhance education and promotion of regular physical activity for hypertensive patients and encourage the adoption of a sustainable healthy lifestyle through community health center programs such as routine exercise and health counseling, in order to help control blood pressure and prevent further complications.